2017
DOI: 10.1007/7854_2017_2
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Species Translational Findings in the Discriminative Stimulus Effects of Ethanol

Abstract: The progress on understanding the pharmacological basis of ethanol’s discriminative stimulus effects has been substantial, but appears to have plateaued in the past decade. Further, the cross-species translational efforts are clear in laboratory animals, but have been minimal in human subject studies. Research findings clearly demonstrate that ethanol produces a compound stimulus with primary activity through GABA and glutamate receptor systems, particularly ionotropic receptors, with additional contribution f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 96 publications
1
6
1
Order By: Relevance
“…Interestingly, however, MK‐801 fully substituted for EtOH in this monkey, suggesting that the glutamatergic cue was guiding the discrimination. This finding is contrary to several other published reports on EtOH discrimination in cynomolgus macaques that have concluded that the GABAergic component is more prominent in macaques relative to rodents across several training doses (Allen et al., ; Grant et al., , ; Stolerman et al., ). One explanation is the relatively large sample size (8 subjects relative to groups of 4 monkeys in previous studies) and choosing the monkeys to be relatively genetically heterogeneous (no common grandparents) allowed this individual difference to be captured.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Interestingly, however, MK‐801 fully substituted for EtOH in this monkey, suggesting that the glutamatergic cue was guiding the discrimination. This finding is contrary to several other published reports on EtOH discrimination in cynomolgus macaques that have concluded that the GABAergic component is more prominent in macaques relative to rodents across several training doses (Allen et al., ; Grant et al., , ; Stolerman et al., ). One explanation is the relatively large sample size (8 subjects relative to groups of 4 monkeys in previous studies) and choosing the monkeys to be relatively genetically heterogeneous (no common grandparents) allowed this individual difference to be captured.…”
Section: Discussioncontrasting
confidence: 99%
“…In conclusion, the data presented here demonstrate that EtOH's discriminative stimulus effects in rhesus monkeys are largely consistent with reports in many other species including pigeons (Grant and Barrett, ), rats (Shelton and Balster, ), mice (Shelton and Grant, ), squirrel monkeys (Platt et al., ), cynomolgus macaques (Grant, ; Grant et al., ; Vivian et al., ; Helms and Grant, ), and humans (Duka et al., ) (for reviews, see Allen et al., ; Grant and Bennett, ; Stolerman et al., ). Additionally, we have conducted a thorough blood EtOH time course with 15‐minute sampling intervals during the rising phase of BEC to capture the time and value of peak BEC following low and moderate EtOH doses.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Taken together, these studies suggest that mGlu receptor signaling can modulate (but not mediate) the interoceptive effects of ethanol, as ligands for these receptors neither substitute nor abolish ethanol’s discriminative stimulus. 177 In contrast, NMDA receptor antagonists and GABAa receptor agonists can completely substitute for the discriminative stimulus effects of ethanol. 178 Interestingly, mGlu 5 may modulate the discriminative stimulus effects of ethanol through downstream interactions with the GABAa receptor.…”
Section: Mglu Receptor Behavioral Pharmacologymentioning
confidence: 99%